Experimental Measurement of a UAV Propeller's Thrust - Patrik Kósa*; Marián Kišev; Lukáš Vacho; Ladislav Tóth; Martin Olejár; Marta Harničárová; Jan Valíček; Hakan Tozan (Tehnički Vjesnik, 2022)
At present, there are several types of propellers in the field of the use of Unmanned Aerial Vehicles (UAVs) with unknown parameters, where it is necessary to provide information about their thrust, current consumption and maximal rotational speed (RPM). Commonly used methods for measurement of a propeller's thrust are mostly based on the usage of a single purpose system, on short measurements without data storage or on inaccurate sensors. The goal of this article is to develop a universal experimental measuring system for more accurate measurement of propeller's parameters (thrust, current consumption, maximal RPM). For more accurate measurement, the battery voltage, temperature and humidity of the environment were also measured. To acquire, measure and store the data safely on a micro SD card, a processing circuit based on an ATmega2560 microcontroller was developed. This innovative approach allowed to analyse the behaviour of the propeller and to measure the dependencies of the RPM on pulse width, of the current on RPM and of the thrust on RPM at different input conditions. The measurements have shown that the dependencies can be approximated by cubic functions. The mathematical description allows predicting the behaviour of the propeller in unmeasurable conditions.